Greetings: Innovations in Morning Greetings - Reni Amiliya; Ruliana Fajriati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
Morning greetings are an important part of creating a positive atmosphere for children at school. At TK Hasanah Pekanbaru, an innovation was introduced by applying varied greetings to allow children to express themselves freely when greeting their teacher. This study aims to explore the impact of varied greetings on the emotions and enthusiasm of early childhood learners. The research used a qualitative descriptive method with observation and documentation techniques. The results show that varied greetings help children feel more appreciated, confident, and excited to join learning activities. Moreover, teachers can more easily understand children’s emotions from the greetings they choose. Options like hugs, high-fives, love symbols, or hand waves allow children to greet according to their mood. This activity also teaches social-emotional values such as love, empathy, and self-protection. In a simple way, this activity brings a significant positive impact to the school environment, making it warmer and more joyful.